Enabling modeling of waterlogging impact on wheat - Nóia-Júnior, Rogério de S.; Stocca, Valentina; Martre, Pierre; Shelia, Vakhtang; Deswarte, Jean-Charles; Cohan, Jean-Pierre; Piquemal, Benoît; Dutertre, Alain; Slafer, Gustavo A.; Zhang, Zhentao; Van Der Velde, Marijn; Kim, Yean-Uk; et al. (Elsevier, 2025)
Most crop simulation models do not consider the effect of waterlogging despite its importance for crop performance. Here, we reviewed the impact of waterlogging during different wheat phenological stages on grain number per unit area, average grain size, and grain yield. Episodes of waterlogging from the onset of tillering to anthesis result in fewer, and during grain filling in lighter grains. To simulate such impacts, we implemented a new waterlogging module into the wheat crop simulation model DSSAT-NWheat, accounting for the effects of waterlogging on wheat root growth, biomass growth, and potential average grain size. The model incorporating the new waterlogging routine was tested using data from a controlled experiment, and it reasonably reproduced wheat yield responses to pre-anthesis waterlogging. A sensitivity analysis showed that the simulated impact of waterlogging on above ground biomass and roots, as well as leaf area index, grain number, and grain yield varied with phenological stages. The simulated crop was most sensitive to pre-anthesis waterlogging, consistent with experimental studies. The new waterlogging-enabled crop model is an initial attempt to consider the impact of excess rainfall and waterlogging on crop growth and final grain yield to reduce model uncertainties when projecting climate change impacts with increasing rainfall intensity.
Keywords: NWheat; DSSAT; excess of water; grain number; grain size; wheat crop simulation model